2021
DOI: 10.17575/psicologia.v35i1.1448
|View full text |Cite
|
Sign up to set email alerts
|

Violência na intimidade: Crenças da comunidade Africana Lusófona residente em Portugal

Abstract: Este estudo teve como objetivo identificar as crenças da comunidade luso-africana, residente em Portugal, sobre a violência na intimidade. Os participantes (n=70) responderam a um questionário online, adaptado da Escala de Crenças sobre a Violência Conjugal. Os resultados apontaram para uma reduzida legitimação da violência, na intimidade, sendo a “pequena” violência a mais legitimada. Os participantes do sexo masculino, sem contacto com a problemática e que avaliaram os episódios como “não graves” apresentara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…This belief may restrain the victims from seeking help, which constitutes a barrier to the policies that prevent IPV because these behaviors are still culturally legitimized (Almeida et al 2023;Alves et al 2019;Barocas et al 2016;Shen 2014). For example, Mendes and Cláudio (2010) observed that the legitimation of violence mainly results from dysfunctional beliefs that excuse abusive behaviors, which have been internalized since very early influencing behavior (Gonçalves et al 2021;Silva 2017). According to , the complexity of human relations has a strong contribution to the main conceptions of violence, making it difficult to define and agree about externalization as being violent or not (Ventura et al 2013).…”
Section: Beliefs Ipv and Gendermentioning
confidence: 99%
“…This belief may restrain the victims from seeking help, which constitutes a barrier to the policies that prevent IPV because these behaviors are still culturally legitimized (Almeida et al 2023;Alves et al 2019;Barocas et al 2016;Shen 2014). For example, Mendes and Cláudio (2010) observed that the legitimation of violence mainly results from dysfunctional beliefs that excuse abusive behaviors, which have been internalized since very early influencing behavior (Gonçalves et al 2021;Silva 2017). According to , the complexity of human relations has a strong contribution to the main conceptions of violence, making it difficult to define and agree about externalization as being violent or not (Ventura et al 2013).…”
Section: Beliefs Ipv and Gendermentioning
confidence: 99%